As concepções de sujeito e desenvolvimento na forma de organização da aprendizagem de história no Brasil: Um estado da arte das pesquisas (2010-2021) - Brandão, Hilma Aparecida (2024)
The end of the 20th century and the beginning of the 21st century presented an education model based on democratic and liberal concepts, which resulted in a process of intensified control over teachers and students, based on the implementation of meritocratic, coercive and punitive instruments, such as external evaluations, bonuses for good results and punishments with displaying low grades on school doors, presence of a tutor, among others. This model results in a loss of the human quality of school learning. Furthermore, in the Bachelor's and Teaching Degree Courses in History, although it is a positive aspect, the privilege given to research comes at the cost of sacrifice; there is a lack of preparatory subjects for classroom performance, prioritizing research to the detriment of pedagogical subjects. Such concerns in the exercise of the profession acquired new meaning with discussions and problematizations within the Study and Research Group on Developmental Didactics and Teacher Professionalization (GEPEDI), resulting in theoretical tools that made it possible to construct the object of the research resulting in this thesis entitled “The conceptions of subject and development in the form of organization of history learning in Brazil: a state of the art of research (2010-2021)”. Starting from the understanding that the form of organization of learning must be one that promotes human development, the question that guided the research carried out was how to think about the subjective processes present in psychic development, from the category of subject and development, in the Perspective of the Theory of Study Activity from the angle of the Theory of Subjectivity? The general objective is to present a theoretical construction, intertwining two references, for a type of History learning, in which the goal is the formation and development of the subject (in the approach of Repkin and the theory of subjectivity) and as content the self-transformation of the student as a subject of the study activity. The research was based on the perspective of Developmental Learning and the Theory of Subjectivity. The concept of subject acquired centrality in the research, but the concepts of development, study activity, subjectivity, subjective configurations, among others, were also used. The conception of subject outlined by Developmental Didactics and the Theory of Subjectivity was assumed, using the state of the art as a resource to contextualize the didactic approaches of history and their limits for the development of the subject, between the periods of 2010 to 2021. The constructive-interpretative method of González Rey contributed to the analyses. The data were obtained from the Directory of Research Groups - CNPq Lattes Platform. The result shows us a situation that points to the growth of productions on the subject, revealing the increase in interest in issues related to the learning of History, but with a focus on teaching, issues related to the curriculum, documentary sources, content, heritage, or the field of historical education, but without focusing on the relationship that exists between learning and psychic development and, even less, on the subjective processes inherent to this process. In view of this result, we defend the need for a didactic proposal focused on the learning of History, which considers not only the student's capacity for psychic development, but also the subjective processes inherent to this development, for which the understanding of the subject and development gain a much more complex meaning than what has been addressed in research on the subject.